2020
DOI: 10.1093/mnras/staa2049
|View full text |Cite
|
Sign up to set email alerts
|

The relation between the diffuse X-ray luminosity and the radio power of the central AGN in galaxy groups

Abstract: Our understanding of how AGN feedback operates in galaxy clusters has improved in recent years owing to large efforts in multi-wavelength observations and hydrodynamical simulations. However, it is much less clear how feedback operates in galaxy groups, which have shallower gravitational potentials. In this work, using very deep VLA and new MeerKAT observations from the MIGHTEE survey, we compiled a sample of 247 X-ray selected galaxy groups detected in the COSMOS field. We have studied the relation between th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 58 publications
7
24
0
Order By: Relevance
“…The properties of group-central radio galaxies are closely linked to the IGrM. Both groups and clusters show a correlation between X-ray luminosity and the radio luminosity of the central source [189,196,197]. In clusters, central radio source luminosity is observed to be higher in systems with cooling times <10 9 yr [198] and, in groups, it appears that radio jets are more common in the central galaxies of groups with short central cooling times, low t cool /t ff ratios, and declining central temperature profiles [106].…”
Section: Interaction Between Radio Sources and The Igrmmentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of group-central radio galaxies are closely linked to the IGrM. Both groups and clusters show a correlation between X-ray luminosity and the radio luminosity of the central source [189,196,197]. In clusters, central radio source luminosity is observed to be higher in systems with cooling times <10 9 yr [198] and, in groups, it appears that radio jets are more common in the central galaxies of groups with short central cooling times, low t cool /t ff ratios, and declining central temperature profiles [106].…”
Section: Interaction Between Radio Sources and The Igrmmentioning
confidence: 99%
“…However, the population of group-central radio galaxies includes much larger objects, some of which extend to very large radii, well beyond the cool core, and even into the outskirts of their groups. Pasini et al [197] show that radio galaxies larger than 200 kpc are more common in groups than clusters, and the largest radio galaxies are located in groups, probably because the IGrM is less able to confine their growth than the ICM. There is also evidence from new radio surveys, with greater sensitivity to extended diffuse emission, that giant radio galaxies may be more common, in general, than previously believed [201].…”
Section: Giant Radio Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the large number of upper limits, we relied on statistical tests, such as the partial correlation Kendall's τ test and the scrambling test, to show that the correlation is not produced by selection effects in the radio band. -Converting the 144 MHz power of radio galaxies to 1.4 GHz, we compared our results with the correlation between the Xray luminosity and the 1.4 GHz power of a COSMOS galaxy groups sample first investigated by Pasini et al (2020). We found that the two samples are in good agreement based on a Kolmogorov-Smirnov test that, under the null-hypothesis that the samples are drawn from the same parent distribution, gives p = 0.41.…”
Section: Discussionmentioning
confidence: 83%
“…To ascertain if the correlation is genuinely detected, we performed the partial correlation Kendall's τ (Akritas & Siebert 1996) test. This tool has already been used in a number of papers (e.g., Ineson et al 2015;Pasini et al 2020) to test correlations in the presence of upper limits and redshift-dependence. The algorithm estimates the null-hypothesis probability that selection effects are producing the correlation.…”
Section: Correlation Between X-ray and 144 Mhz Radio Luminositymentioning
confidence: 99%